New Integral Operator for Analytic Functions - H. Özlem Güney; Shigeyoshi Owa; Adel A. Attiya (Journal of Function Spaces)
Let Apn be the class of functions fz given by fz=zp+ap+nzp+n+ap+n+1zp+n+1+⋯ which are analytic in the open unit disk U. For fz∈Apn, new integral operators O−jfz and Ojfzj=0,1,2,⋯. are considered. The operators O−jfz and Ojfz satisfy OjO−jfz=O−jOjfz=fz and O−j∗Ojfz=Oj∗O−jfz=f∗fz for the convolution ∗ of O−jfz and Ojfz. In the present paper, the dominants for both operators O−jfz and Ojfz and subordinations for O−jfz and Ojfz are discussed. Also, new subclass Tpγm,δ,ρ;m,j concerning with m different boundary points is defined and discussed. Moreover, some interesting problems of Tpγm,δ,ρ;m,j associated with Ojfz are obtained. Furthermore, some interesting examples for our results are considered.